ANALISIS KESULITAN MEMBACA KOSAKATA PADA MATA PELAJARAN BAHASA INDONESIA KELAS III UPT SDN 3 TAROWANG KABUPATEN JENEPONTO - Nurwahda; Muh. Aidil Sudarmono R; Andi Hasriani; Subaedah; Martini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze vocabulary reading difficulties, the causes, and efforts to address them in the Indonesian language subject of third-grade students at UPT SDN 3 Tarowang, Jeneponto Regency. The study used a qualitative approach with a descriptive type. The research subjects consisted of teachers and students, with a focus on 10 students who experienced reading difficulties. Data collection techniques were through observation, interviews, and documentation. The results showed that students experienced difficulties in recognizing letters, combining letters into words, and reading fluently. Factors causing vocabulary reading difficulties include low interest in reading, weak memory, a less supportive family environment, and learning methods that are not optimally varied. Efforts made by teachers include regular reading practice, special mentoring for students, the application of shared reading methods, the use of interesting learning media, and providing learning motivation. Continuous efforts and the development of more varied learning methods are needed to optimally improve students' vocabulary reading abilities.